2007
DOI: 10.1002/asna.200710867
|View full text |Cite
|
Sign up to set email alerts
|

On the solar rotation and activity

Abstract: Thei nteractionb etween differentialr otationa nd magnetic fieldsi nthe solar convectionz one wasr ecently modelledb y Brun ( 2004). Onec onsequence of that model is that theM axwells tresses can oppose theR eynolds stresses, and thus contribute to thet ransport of thea ngular momentum towards thes olar poles, leading to ar educed differentialr otation. So,when magnetic fieldsare weaker,amore pronounced differentialrotationcan be expected, yielding ahigher rotation velocity at lowlatitudes takenonthe average. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…Some indication of the weakening of the solar differential rotation in the presence of strong magnetic field have been observed recently (Ambroz 2004), with a weaker zonal flow during the peak of magnetic activity (see also Brajsa et al 2007). Eddy et al (1976) have also shown that during the Maunder minimum the Sun had a greater angular velocity contrast.…”
Section: The Influence Of a Dynamo Induced Magnetic Field On The Meanmentioning
confidence: 71%
“…Some indication of the weakening of the solar differential rotation in the presence of strong magnetic field have been observed recently (Ambroz 2004), with a weaker zonal flow during the peak of magnetic activity (see also Brajsa et al 2007). Eddy et al (1976) have also shown that during the Maunder minimum the Sun had a greater angular velocity contrast.…”
Section: The Influence Of a Dynamo Induced Magnetic Field On The Meanmentioning
confidence: 71%
“…), we will investigate the relationship between the parameters of the solar rotation and the solar activity using the monthly and yearly values of the solar rotation parameters presented in this work. In this way, we would like to complement some earlier studies of the coronal rotation variation (e.g., Nash et al 1988;Rybák 1994Rybák , 2000Altrock 2003;Brajša et al 2007;Gissot 2009, and references therein) and to compare those results for coronal structures with those obtained using other tracers and methods in different time periods (Table 16 in the present paper).…”
Section: Discussionmentioning
confidence: 82%
“…23, while the whole time period (1998−2006) embraces most of the activity maximum of the same solar cycle. The observed north-south rotational asymmetry can be interpreted in the framework of a model of interdependence of solar rotation and activity, taking into account the balance between Reynolds and Maxwell stresses (Brun 2004;Brun et al 2004;Brajša et al 2006Brajša et al , 2007. During most of the 23rd solar cycle, the southern solar hemisphere was more active (Temmer et al 2006, their Fig.…”
Section: The North-south Asymmetry Of the Solar Rotation Compared Witmentioning
confidence: 99%
“…Discrepancies for the same tracers (for various authors) may be due to the time intervals and lengths of data included. Increasing evidence (Balthasar et al 1986;Bai 2003;Brajša et al 2006Brajša et al , 2007Balthasar 2007;Heristchi & Mouradian 2009) suggests that the solar differential rotation changes from cycle to cycle and even within one cycle. Bouwer (1992) claimed that precise rotation periods between 27 and 28 days persist only for a short time, sometimes only for a few solar rotations.…”
Section: Introductionmentioning
confidence: 99%